The BASES expert statement on measurement of muscle strength with isokinetic dynamometry - Baltzopoulos, V., B.; King, M.; Gleeson, N.; de Ste Croix, M. (The Sport and Exercise Scientist, 2012)
To obtain accurate joint moment-angle-angular velocity data for the assessment of strength and safeguard validity and reliability of strength measurements it is important that: • dynamometers are serviced regularly and calibrated according to recommended techniques using a range of weights to confirm moment measurements and accurate goniometers are used to confirm angle measurements • the participant is positioned and stabilised appropriately on the dynamometer including adjacent joints of biarticular muscles • joint and dynamometer axes are aligned under active and not passive conditions, near the anticipated maximum moment position and separately for reciprocal actions (e.g., extension and flexion tests) • gravity and any other relevant correction techniques are applied • an appropriate testing protocol with standardised procedures for habituation, feedback and motivation is used • maximal range of motion is set, with preloading if necessary, to allow the participant to reach maximum voluntary activation and the preset joint velocity and to maximise the isokinetic phase • angular velocity is monitored and only isovelocity regions of each trial are used for subsequent analysis(velocity within 10% of the preset value) • acceleration period data and derived parameters (such as `torque acceleration energy`) should not be used because they are affected by the different velocity control mechanisms of each dynamometer • stabilisation and joint axes alignment methods, correction techniques, test parameters, and isovelocity assessment method in high angular velocity tests must be reported explicitly.